2017
DOI: 10.22178/pos.27-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Planck’s Constant using Light Emitting Diodes

Abstract: Abstract. Planck's constant is named after Max Planck, a nineteenth-century physicist who first described it by relating it as E=h usual meanings. It is a relationship used when comparing a quantum of energy absorbed to that emitted during electron transitions which can be extended to emission by light-emitting diodes. The purpose of this study was to determine Planck's constant using the energy needed to excite free electrons in a light emitting diode. When a light-emitting diode is switched on, electrons re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…It also implies that the fill factor of this solar cell will decrease as thickness increase and the consequence will be that the cell internally consumes power reducing efficiency after a certain peak thickness. Similar observations were re-ported by the experimental result by [16], who concluded that recombination expedites with increasing thickness.…”
Section: Figure 4 -Influence Of Thickness On Open-circuit Voltage Persupporting
confidence: 83%
See 1 more Smart Citation
“…It also implies that the fill factor of this solar cell will decrease as thickness increase and the consequence will be that the cell internally consumes power reducing efficiency after a certain peak thickness. Similar observations were re-ported by the experimental result by [16], who concluded that recombination expedites with increasing thickness.…”
Section: Figure 4 -Influence Of Thickness On Open-circuit Voltage Persupporting
confidence: 83%
“…The material optical parameters used in SCAPS-1D simulation were selectively picked from published articles by [35] and a number of supporting optoelectronic theories. The other optical constant and absorption coefficients for both CH3NH3PbI3 and Ag:CH3NH3PbI3 were obtained from [16]. A summary of some of these optical parameters are as tabulated in tables 1.…”
Section: Methodsmentioning
confidence: 99%
“…There are numerous methods to determine the Planck's constant [2][3][4][5][6][7][8][9][10][11][12][13]. In the undergraduate laboratories the Planck's constant is experimentally calculated using light emitting diode (LEDs) of different colours.…”
Section: Introductionmentioning
confidence: 99%
“…Mosiori et al and Eagan [4,14] used a spectrophotometer to find the wavelength of the light being emitted by the LEDs and used these values to experimentally find the Planck's constant. Nieves et al [10] used a monochromator to determine the respective wavelengths of the light emitted by the LEDs.…”
Section: Introductionmentioning
confidence: 99%